Analisis Kelayakan Kegrafikan Buku Teks Bahasa Cerdas Berbahasa Indonesia untuk SMA Kelas X Kurikulum 2013 Revisi Terbitan Erlangga - Angela Suryani Putri; Apri Winda Hafifah; Chaterine Br. Sitepu; Avinda Elsa Febriani; Bintang Andi Putra; Muhammad Mukhlis (UIR Press, 2022)
The purpose of this study was to describe the feasibility of an Indonesian-language Smart Textbook for SMA class X 2013 Revised Curriculum published by Erlangga. This research is a descriptive study using a qualitative research design. The research method was chosen to answer the research objective, namely to describe the feasibility of the Indonesian-language Smart Textbook for SMA class X Revised 2013 Curriculum published by Erlangga. Data collection techniques using the method of observation (observation). The data analysis technique in this study was carried out descriptively based on the BSNP/PusBuk.PP category table. 19/2005 Article 43 paragraph (5) states that the appropriateness of the content, language, presentation, and graphics of textbooks is assessed by BSNP and stipulated by a Ministerial Regulation. The aspect of feasibility that is observed is the feasibility of graphics. The instrumental items to be analyzed consist of: (1) Book Format Size; (2) Leather Part Design; (3) Contents Section Design; (4) Paper Quality; (5) Print Quality and; (6) Volume Quality.